Fruit abortion, developmental selection and developmental stability in Quercus ilex. - Díaz, Mario; Møller, Anders P; Pulido, Fernando J (Oecologia, 2003)
Fruit abortion has been hypothesized to be a parental means of selective removal of propagules with low viability. In particular, aborted zygotes have been suggested to have developmentally deviant phenotypes, and surviving offspring may therefore give rise to adults with a developmentally stable phenotype. We tested predictions from this hypothesis using acorns of holm oaks Quercus ilex as a model system. Fecundity of oak trees was negatively related to mean fluctuating asymmetry of leaves, and abortion rates were positively related to leaf fluctuating asymmetry in at least one population. Aborted acorns were asymmetric in 83-99% of cases in three samples, while mature acorns were only asymmetric in 57-78% of cases. Acorn asymmetry was unrelated to germination probability and germination date, and had no significant effect on number of leaves, leaf mass, stem mass, seedling height or leaf area of seedlings. However, acorn asymmetry affected the trade-off between number and size of leaves in seedlings. Seedlings from asymmetric acorns showed a positive relationship between acorn size and number of leaves, but no relationships between acorn size and leaf area, while symmetric acorns showed the opposite. A positive relationship between acorn size and number of leaves in spring was found for naturally emerged seedlings that died during their first summer, whereas the number of leaves produced by surviving seedlings did not depend on acorn size. These findings are consistent with the hypothesis that stressed trees selectively abort propagules of low viability, and that developmental selection acts on a measure of developmental instability of fruits.
Keywords: acorn; Fluctuating asymmetry; Leaf number; Leaf size; Maternal effect

Fruit abortion, developmental selection and developmental stability in Quercus ilex. - Díaz, Mario; Møller, Anders P.; Pulido, Fernando J. (Oecologia, 2003)
Fruit abortion has been hypothesized to be a parental means of selective removal of propagules with low viability. In particular, aborted zygotes have been suggested to have developmentally deviant phenotypes, and surviving offspring may therefore give rise to adults with a developmentally stable phenotype. We tested predictions from this hypothesis using acorns of holm oaks Quercus ilex as a model system. Fecundity of oak trees was negatively related to mean fluctuating asymmetry of leaves, and abortion rates were positively related to leaf fluctuating asymmetry in at least one population. Aborted acorns were asymmetric in 83-99% of cases in three samples, while mature acorns were only asymmetric in 57-78% of cases. Acorn asymmetry was unrelated to germination probability and germination date, and had no significant effect on number of leaves, leaf mass, stem mass, seedling height or leaf area of seedlings. However, acorn asymmetry affected the trade-off between number and size of leaves in seedlings. Seedlings from asymmetric acorns showed a positive relationship between acorn size and number of leaves, but no relationships between acorn size and leaf area, while symmetric acorns showed the opposite. A positive relationship between acorn size and number of leaves in spring was found for naturally emerged seedlings that died during their first summer, whereas the number of leaves produced by surviving seedlings did not depend on acorn size. These findings are consistent with the hypothesis that stressed trees selectively abort propagules of low viability, and that developmental selection acts on a measure of developmental instability of fruits.
The following values have no corresponding Zotero field: accession-num: 12721827
Keywords: acorn; Fluctuating asymmetry; Leaf number; Leaf size; Maternal effect